Estrogenic activity of mixtures in the Salish Sea: The use of high throughput toxicity data with chemical information from fish bile and other matrices - Maya Faber; C. Andrew James; Louisa B. Harding; Denis A. M. da Silva; Ruth M. Sofield (PLoS ONE, 2025)
A subset of anthropogenic chemicals known as contaminants of emerging concern (CECs), are released into aquatic environments through human activities. CECs occur in mixtures, and some may share a common mode of action such as estrogen receptor agonism, which lead to reproductive disturbances in fish. In this study, the estrogenic activity of mixtures was assessed with in vitro high throughput data, which expanded the number of chemicals included in the evaluation. Data were compiled from 16 studies, analyzing 387 CECs (19 estrogen agonists detected), across various matrices including water, wastewater treatment plant effluent, fish and mussel tissue, and fish bile. Novel estrogenic mixture thresholds in water and bile were developed. In one application of the bile thresholds, field sites with elevated exogenous estrogenic activity were identified; thresholds were qualitatively validated using field measures of organism response. Using validated water and bile thresholds in a second application, samples were evaluated to identify mixtures with high, medium, and low estrogenic activity, and individual chemicals were prioritized from those mixtures. Prioritized chemicals were identified as drivers of estrogenic activity (individually exceeding the threshold) or as major or minor contributors (resulting in an exceedance only when combined with other chemicals). Among fish bile samples with medium or high estrogenic activity, 62% of mixture response was explained by chemical drivers rather than mixtures of contributing chemicals. The primary drivers were: estrone, 17β-estradiol, and to some extent, estriol. Bisphenol A was identified as a major contributor.